The informality of the public transport and environmental pollution in the city of Huanuco period 2012 – 2014 - Dionisio Vara, Adler Aurelio (2017)
The survey results that correspond to INFORMAL PUBLIC TRANSPORT AND ENVIRONMENTAL POLLUTION IN THE CITY OF HUÁNUCO “PERIOD 2012 - 2014, show that unemployment with 67.7%, is what determines the growth of the fleet in the Huanuco. We found that most youth are dedicated to public transport as there are other ways to get some sort of suitable employment due tolack of training and professionalism and the second factor is the problem of low-wage jobs (24.7%),reflected primarily in the education sector, teachers in their free time are devoted to I collect ordispersed taxi. Working conditions in the city of Huánuco are inadequate and the few that are nothedging demand of the population. The unemployment caused by the lack of adequate and wellpayingjobs require the citizen to opt for public transport service, thereby generating fleet growthand practice of informality in all its magnitude. The fleet circulating in our city are mostly average20 years old and highly polluting agents this informality with which operate adds. Huánuco in recentdecades has undergone rapid growth of the city, this is accompanied by a set of problems, one ofthem is the public transport system rigged informality generated by unemployment. The gentlementhat offer the service of public transport in the city of Huánuco are person who is between 20-55years of age, represented by 27%. The income of people who are dedicated to public transportservice between 40 and 55 soles a day, it is observed that 30.1% of people receive daily between50-55 daily soles and earning between 40 and 45 soles a day is represented by 29%. In general wecan say that 59.1% earn between 40 and 55 soles a day. There is a culture of informality in the cityof Huánuco, so much so that 87.1% of respondents mentioned that there informality in urban publictransport and there is more than 3000 public transport vehicle units circulating in our city informally.The fleet in the city of Huánuco is growing more units manufacturing time and these units generateemissions of toxic gases, 87.1% of respondents mentioned that there is pollution by mobile unitsproviding public transport for CO2 emissions and by the age they have.